Application of different rates and frequencies of rejuvenator for the treatments of brown bast syndrome on Hevea Brasiliensis - Nik Hashyati, N. H.; Sulaiman, Z.; Salisu, M. A.; Samad, M. Y. A.; Mohamed, M. T. M.; Mokhatar, Mohd Shafar Jefri; Ghani, Zarawi A. B.; Adinan, Azwan (Agricultural Research Communication Centre, 2022)
Background: Brown bast is one of the most serious threats to natural rubber production. It is estimated that brown bast leads to an approximately 15-20% decrease in latex yield production. There is currently no effective method to control this problem and an effort to overcome this problem is in progress by the natural rubber producing countries. Methods: This study evaluated the effect and the most suitable rate and frequency of Rejuvenator application to cure brown bast (latex dryness) and improve latex yield. The Rejuvenator treatment was applied to the selected tree with two different treatment frequencies (every 3 days and every 6 days) and three different Rejuvenator concentrations (5 g/L, 10 g/L and 5 g/L). The Rejuvenator was applied 5 times. Data on latex yield and brown bast cure were then recorded 1 month after the application of the last treatment. The treatments used were T1: No Rejuvenator, T2: 5 g/L of Rejuvenator, T3: 10 g/L of Rejuvenator, T4: 15 g/L of Rejuvenator. Result: Of all the treatment used, T3 (10 g/L) resulted in higher production of latex yield and Hevea bark nutrient concentration (g/t/t) than control. It also gave the highest nutrient content in the bark tissue. The findings of this study reveal that the optimum concentration and frequency of Rejuvenator application were established at 10 g/L every 6 days. More so, the findings explain that inadequate nutrients can be attributed to the brown bast syndrome in rubber plantation which can be prevented with the use of a rejuvenator to the tree’s bark.